Subcellular functions of proteins under fluorescence single-cell microscopy() - Kohnhorst, Casey L. (Biochim Biophys Acta, 2015)
A cell is a highly organized, dynamic, and intricate biological entity orchestrated by a myriad of proteins and their self-assemblies. Because a protein’s actions depend on its coordination in both space and time, our curiosity about protein functions has extended from the test tube into the intracellular space of the cell. Accordingly, modern technological developments and advances in enzymology have been geared towards analyzing protein functions within intact single cells. We discuss here how fluorescence single-cell microscopy has been employed to identify subcellular locations of proteins, detect reversible protein–protein interactions, and measure protein activity and kinetics in living cells. Considering that fluorescence single-cell microscopy has been only recently recognized as a primary technique in enzymology, its potentials and outcomes in studying intracellular protein functions are projected to be immensely useful and enlightening. We anticipate that this review would inspire many investigators to study their proteins of interest beyond the conventional boundary of specific disciplines. This article is part of a Special Issue entitled: Physiological Enzymology and Protein Functions.